ShAYÍR T.QABULOV ShÍǴARMALARÍNDA QOLLANÍLǴAN SÓZ JASAWShÍ QOSÍMTALARDÍŃ STILI - Seydullaeva, Dárigúl Yuldashevna; Seydullaeva, Ayzada Yuldashevna (SCIENCE and SOCIETY, 2026)
The article theoretically highlights the system of word formation in Karakalpak linguistics, its methods, and the history of research, and analyzes the linguistic and stylistic features of word-forming affixes using the works of the renowned writer T.Kabulov as an example. Also, the function of compound words and affixal morphemes formed on the basis of the law of economy of language means in the text in the literary text is determined.